Representaciones sociales que tienen docentes del IPN, Escuela Maternal y UPN, en torno a la didáctica, (2013)
This research project originated from an interest in exchanging ideas and experiences among the Childhood Education Program at Universidad Pedagógica Nacional, the Nursery School, and the pre-school section at Instituto Pedagógico Nacional. Its main objective is to inquire about social representations in relation to didactics; due to the fact that it is in this regard that there is distance from the practices that take place at these three institutions. In addition, the problem and research objectives are presented, followed by the research design, and finally, the findings and conclusions are discussed.